Against Moral Purism - García Gibson, Francisco (2018)
Moral purism is the view that doing evil is never allowed, even as a means to prevent a greater evil. This article assesses two main versions of moral purism and shows that they are implausible. The first version claims that it is always impermissible to choose an option that results in a bad states of affairs, while the second version claims that it is always impermissible to choose an option that is wrong, even if it is only prima facie wrong. I contend that both versions are incomplete, in the sense that they are unable to provide practical guidance for cases in which all available options result in bad states of affairs, or in which all available options are prima facie wrong.